Series de Investigación REOALCEI III. Generación de conocimiento en las ciencias sociales: impacto desde los ciudadanos, las comunidades y las instituciones - Alvarado-Peña, Lisandro José; Antón Chávez, Alina del Pilar; Bueno Fernandez, Mario Mitsuo; Fonseca de Castro, Rafael; Chu González, Elvia Alejandra; Dozal, León; Gaxiola Sosa, Rodrigo Fidel; González Rios, Noemi; Hernandez Silva, José Fernando; Jasso Velazquez, David; León Villalobos, José María; López Varela, Carmen Guadalupe; et al. (High Rate Consulting, 2026)
The book “Generation of Knowledge in Social Sciences: Impact from Citizens, Communities, and Institutions” addresses the complex and multifaceted production of knowledge in contemporary social spheres, examining how different actors influence and are influenced by this process. The text explores the citizen dimension through active citizenship and urban monitoring of green spaces, suggesting proactive community roles in environmental management. Simultaneously, it analyzes the impact of technology, dedicating space to Information and Communication Technologies (ICT) as a driver of competitiveness in Colombia, while examining the double-edged nature of digital connection with issues such as mobile addiction and social isolation in the university setting. Furthermore, the work delves into the impact of these changes in professional and educational environments. It discusses the protection of honor in Peruvian journalism as a legal aspect of information generation and explores Hybrid Education, assessing its psychosocial effects on mental health and the reconfiguration of teaching work. Finally, the book includes a literature review on Artificial Intelligence in Higher Education, closing the thematic circle on how technology and institutions are redefining social knowledge. Together, the book provides a comprehensive view of the social, technological, and legal forces that shape current social science.